The issue of compliance in patients with treatment resistance depressions = Проблема комплаєнсу у хворих з терапевтично резистентними депресіями - Rakhman, L.; Markova, M. (Journal of Education, Health and Sport, 2015)
Rakhman Lyudmyla, Markova Marianna. The issue of compliance in patients with treatment resistance depressions = Проблема комплаєнсу у хворих з терапевтично резистентними депресіями. Journal of Education, Health and Sport. 2015;5(8):111-118. ISSN 2391-8306. DOI 10.5281/zenodo.27441 http://dx.doi.org/10.5281/zenodo.27441 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A111-118 https://pbn.nauka.gov.pl/works/605290 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. UDK: 616.89-008.19:615.015.46:614.253.8 THE ISSUE OF COMPLIANCE IN PATIENTS WITH TREATMENT RESISTANCE DEPRESSIONS Проблема комплаєнсу у хворих з терапевтично резистентними депресіями Lyudmyla Rakhman¹, Marianna Markova² Л. Рахман, M. Maркова ¹Danylo Halytskiy Lviv National Medical University, Lviv, Ukraine ²Kharkiv Medical Academy of Post-graduate Education, Kharkiv, Ukraine Summary The study revealed that the main causes of partial or non-compliance in patients with treatment resistance depression (TRD) at the beginning of therapy are the side effects of medications, as well as a significant reduction in self-esteem of patients. In period of discharge from hospital major factor for the lack of compliance is a low level of knowledge about factors and mechanisms of TRD and lowered financial opportunity for ensuring required maintenance therapy. The cooperation between doctor and patient, so-called "therapeutic alliance" is one of the most important aspects of treatment effectiveness in TRD. Keywords: compliance, treatment resistance depression, treatment, remission. Резюме Дослідження показало, що основними причинами часткового або відсутнього комплаєнсу у хворих з терапевтично резистентними депресіями (ТРД) на початку терапії є побічні ефекти лікарських препаратів, а також значне зниження самооцінки пацієнтів. У період виписки зі стаціонару основними факторами дефіциту комплаєнсу є низький рівень знань про фактори розвитку і механізми TРД і знижена фінансова спроможність пацієнтів для забезпечення необхідної підтримуючої терапії. Співпраця між лікарем і пацієнтом, так званий "терапевтичний альянс", є одним з найбільш важливих аспектів ефективності лікування хворих, які страждають на ТРД. Ключові слова: комплаєнс, терапевтично резистентні депресії, лікування, ремісія. Резюме Проблема комплаенса у больных терапевтически резистентными депрессиями. Исследование показало, что основными причинами частичного или отсутствующего комплаенса у больных терапевтически резистентными депрессиями (ТРД) в начале терапии являются побочные эффекты лекарственных препаратов, а также значительное снижение самооценки пациентов. В период выписки из стационара основными факторами дефицита комплаенса является низкий уровень знаний о факторах развития и механизмы ТРД и низкая финансовая способность пациентов для обеспечения необходимой поддерживающей терапии. Сотрудничество между врачом и пациентом, так называемый "терапевтический альянс", является одним из наиболее важных аспектов эффективности лечения больных, страдающих ТРД. Ключевые слова: комплаенс, терапевтически резистентные депрессии, лечение, ремиссия.